Fractional anisotropy from diffusion tensor imaging correlates with acute astrocyte and myelin swelling in neonatal swine models of excitotoxic and hypoxic‐ischemic brain injury. Issue 10 (15th February 2021) - Lee, Jennifer K.; Liu, Dapeng; Jiang, Dengrong; Kulikowicz, Ewa; Tekes, Aylin; Liu, Peiying; Qin, Qin; Koehler, Raymond C.; Aggarwal, Manisha; Zhang, Jiangyang; Martin, Lee J.
Abstract: The specific cytopathology that causes abnormal fractional anisotropy (FA) and mean diffusivity (MD) from diffusion tensor imaging (DTI) after neonatal hypoxia‐ischemia (HI) is not completely understood. The panoply of cell types in the brain might contribute differentially to changes in DTI metrics. Because glia are the predominant cell type in brain, we hypothesized that changes in FA and MD would signify perturbations in glial microstructure. Using a 3‐Tesla clinical scanner, we conducted in vivo DTI MRI in nine neonatal piglets at 20–96 h after excitotoxic brain injury from striatal quinolinic acid injection or global HI. FA and MD from putamen, caudate, and internal capsule in toto were correlated with astrocyte swelling, neuronal excitotoxicity, and white matter injury. Low FA correlated with more swollen astrocytes immunophenotyped by aquaporin‐4 (AQP4), glial fibrillary acidic protein (GFAP), and glutamate transporter‐1 (GLT‐1). Low FA was also related to the loss of neurons with perineuronal GLT‐1+ astrocyte decorations, large myelin swellings, lower myelin density, and oligodendrocyte cell death identified by 2′, 3′‐cyclic nucleotide 3′‐phosphodiesterase, bridging integrator‐1, and nuclear morphology. MD correlated with degenerating oligodendrocytes and depletion of normal GFAP+ astrocytes but not with astrocyte or myelin swelling. We conclude that FA is associated with cytotoxic edema in astrocytes and oligodendrocyte processes as well as myelin injury at the cellular level. MD can detect glial cell death and loss, but it may not discern subtle pathology in swollen astrocytes, oligodendrocytes, or myelin. This study provides a cytopathologic basis for interpreting DTI in the neonatal brain after HI. Abstract : In neonatal piglets with encephalopathy from excitotoxic brain injury, fractional anisotropy from diffusion tensor imaging correlates with swollen astrocytes immunophenotyped by glutamate transporter‐1 (GLT‐1) and normal neurons with perineuronal GLT‐1+ astrocyte decorations in the striatum.